Lacosamide as treatment for partial epilepsy: mechanisms of action, pharmacology, effects, and safety - Christoph Kellinghaus (Dove Medical Press, 2009)
Christoph KellinghausDepartment of Neurology, Klinikum Osnabrück, GermanyAbstract: Lacosamide (LCM) is a novel agent that has been developed as an antiepileptic drug. In vitro studies suggest that LCM modulates voltage-gated sodium channels by enhancing their slow inactivation. In addition, LCM seems to interact with collapsin-response mediator protein 2 and thus may mediate neuronal plasticity. LCM has an elimination half-life of 13 hours, no relevant protein binding, and does not induce or inhibit enzymes of the cytochrome P450 system. No clinically significant drug–drug interactions have been discovered as yet. Experimental data suggest anticonvulsant as well as analgesic effects. Large clinical studies have demonstrated its efficacy for treatment of patients with partial seizures. LCM is well tolerated, and the most common adverse events are unspecific central nervous system and gastrointestinal effects such as dizziness, vertigo, nausea, and headache. LCM is approved for treatment of partial seizures with or without secondary generalization in the United States and the European Union within a dose range of 200 to 400 mg per day, administered twice daily. In addition to the oral formulations, an intravenous infusion solution is available.Keywords: lacosamide, epilepsy, antiepileptic drug